Large-scale manufacturing and characterization of CMV-CD19CAR T cells - Stephen J Forman; Xiuli Wang; Ryan Urak; Miriam Walter; Min Guan; Tianxu Han; Vibhuti Vyas; Sheng-Hsuan Chien; Brenna Gittins; Mary C Clark; Sally Mokhtari; Angelo Cardoso; et al. (Journal for ImmunoTherapy of Cancer)
Background Adoptive transfer of CD19-specific chimeric antigen receptor (CD19CAR) T cells can induce dramatic disease regression in patients with B cell malignancies. CD19CAR T cell therapy may be limited by insufficient engraftment and persistence, resulting in tumor relapse. We previously demonstrated a proof of principle that cytomegalovirus (CMV)-specific T cells can be isolated and enriched prior to CD19CAR transduction to produce CMV-CD19CAR T cells, and that these CMV-CD19CAR T cells can be expanded in vivo through CMV vaccination, resulting in better tumor control in a murine model. Here we developed a clinical platform for generating CMV-CD19CAR T cells.Methods Peripheral blood mononuclear cells (PBMCs) collected from CMV-seropositive healthy donors were stimulated with a good manufacturing practices-grade PepTivator overlapping CMVpp65 peptide pool and enriched for CMV-responsive interferon γ (IFNγ)+T cells using IFNγ Catchmatrix, within the CliniMACS Prodigy Cytokine Capture System (Miltenyi Biotec). Resulting CMV-specific T cells were transduced with a lentiviral vector encoding a second generation CD19R:CD28:ζ/EGFRt CAR and expanded with interleukin 2 (IL-2) and IL-15 for 15 days before characterization.Results CMV-specific T cells were enriched from 0.8%±0.5 of input PBMC to 76.3%±11.6 in nine full-scale qualification runs (absolute yield of 4.2±3.3×106 IFNγ+T cells from an input of 1×109 PBMCs). Average CD19CAR transduction efficiency of CMV-specific T cells was 27.0%±14.2 in the final products, which underwent rapid expansion, resulting in a total cell dose of 6.2±0.9 × 106 CD19CAR-tranduced T cells with CMV specificity (ie, functionally bispecific). CMV-CD19CAR T cells were polyclonal, expressed memory markers but had low expression of exhaustion markers, responded to both CD19 and CMVpp65 stimulation with rapid proliferation and exhibited antigen-specific effector functions against both CD19-expressing tumors and CMVpp65 antigen. The final products passed release criteria for clinical use.Conclusions We demonstrated the feasibility of our large-scale platform for generating CMV-CD19CAR T cells for clinical application. We plan to initiate a clinical trial at City of Hope using CMV-CD19CAR T cells for patients with intermediate/high-grade B cell non-Hodgkin’s lymphoma immediately after autologous hematopoietic cell transplantation followed by vaccination with a novel CMV vaccine based on Modified Vaccinia Ankara (Triplex) 28 days and 56 days post-T cell infusion.